GEDUNG OLAH RAGA BOLA BASKET DI KOTA BANJARBARU - Suantoro, Bintang; Mutia, Indah (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
The newly established capital of South Kalimantan, Banjarbaru, has experienced rapid growth in education, economy, and governance. However, it currently lacks sufficient sports facilities, with only a type C basketball sports hall with a capacity of less than 1000 people. The purpose of this design is to create a type B Basketball Sports Hall using a modern functional approach that not only prioritizes comfortable and standard-compliant space functionality but also adopts modern architectural concepts. The resulting design aims to provide not only a basketball court and seating area but also is supported by clinic and gym facilities to support player preparation before training and aid in physical and mental recovery. The basketball court is placed centrally for spatial organization efficiency and circulation, accompanied by supporting facilities around it. Modern architectural concepts are integrated into the design by incorporating characteristics such as dominant box-shaped forms with grid structures and the use of concrete and steel materials. Thus, this building design not only focuses on physical aspects but also considers the holistic needs of its users.